Fishery productivity and its contribution to overall agricultural production in the Lower Mekong River Basin - Mainuddin, Mohammed; Kirby, Mac; Chen, Yun (2011)
The Mekong River and its ecosystems have one of the most diverse and abundant fisheries in the world. The fisheries are a major factor in the well-being and livelihoods of the nearly 70 million people especially in the lower Mekong Basin who derive their livelihood from fishery and also depend on fish and other aquatic animals for nutrition and food security. Fishery production and value have been the subject of many studies and some data are available from national and international statistical databases. None of these, however, offer a reliable, consistent set of data on the spatial and temporal trends at a similar level of resolution across the basin. Because of the shortcomings in the data, there are major uncertainties in estimates of fishery production and its value in the four countries of the lower Mekong Basin: Cambodia, Lao PDR, Thailand and Viet Nam. Catch surveys tend to underestimate the production, while consumption-based estimates are regarded as more reliable indicators. We combined official statistics with several consumption-based estimates to examine the spatial and temporal trends in production and value of capture fish and aquaculture. The highest estimates of production range from 42 kg/capita/year in the Lao PDR to 65 kg/capita/year in Cambodia, the latter figure being comparable to consumption in Japan. Production is dominated by capture fisheries in Cambodia (where it is concentrated around the Tonle Sap and the Mekong River), Laos and Thailand. In Viet Nam, aquaculture dominates production and is concentrated around the main rivers in the delta and along the coastal strip. While there are uncertainties in the data, it appears that production until 2005 from capture fisheries has not increased significantly in all the four lower Mekong countries. In aquaculture, there has been a large increase in production in the Mekong Delta region of Viet Nam since about 2000. The highest estimates of value, using consumption-based estimates of production, mainly from capture fisheries, give an annual value of about US$3 billion. Other estimates place the overall value somewhat lower. The value is probably not changing greatly with time. Aquaculture in Viet Nam is rapidly increasing in value, matching the increase in production, and in 2005 was worth over US$1 billion. The contribution of the fishing sector to overall agricultural production (crops, livestock and fish) is small in the Lao PDR and Thailand, but larger in Cambodia and growing in Viet Nam. The demand for fish products will rise in the future, partly as a result of increasing population in the region and partly as a result of increasing incomes. Moreover, there may also be a continuing rise in the export of fish products. The lower Mekong fisheries face threats to production from changed water availability and quality, dams and other barriers affecting fish migration and productivity, and overfishing. If the increased demand is to be met, these threats must be managed so that production, especially of wild capture fish, does not decline. The increasing demand appears unlikely to be met through an increase in production of capture fisheries. The current rapid growth of aquaculture, if it can be maintained, does appear capable of meeting the demand. There are neither quantitative estimates of the limits to growth of this industry, however, nor whether it will pose risks for the capture fisheries since aquaculture needs huge quantities of fish fry as feed. Rice-fish farming may also contribute to increased fish production, but again the impact appears not to have been quantified